Global characteristics and outcomes of autologous hematopoietic stem cell transplantation for newly diagnosed multiple myeloma: a study of the worldwide network for blood and marrow transplantation (WBMT) - Garderet, Laurent; Gras, Luuk; Koster, Linda; Baaij, Laurien; Hamad, Nada; Dsouza, Anita; Estrada-Merly, Noel; Hari, Parameswaran; Saber, Wael; Cowan, Andrew J.; Iida, Minako; Okamoto, Shinichiro; et al. (American journal of hematology, 2024)
Autologous hematopoietic cell transplantation (AHCT) is a commonly used treatment in multiple myeloma (MM). However, real-world global demographic and outcome data are scarce. We collected data on baseline characteristics and outcomes from 61 725 patients with newly diagnosed MM who underwent upfront AHCT between 2013 and 2017 from nine national/international registries. The primary endpoint was overall survival (OS), and the secondary endpoints were progression-free survival (PFS), relapse incidence (RI) and non-relapse mortality (NRM). Median OS amounted to 90.2 months (95% CI 88.2-93.6) and median PFS 36.5 months (95% CI 36.1-37.0). At 24 months, cumulative RI was 33% (95% CI 32.5%-33.4%) and NRM was 2.5% (95% CI 2.3%-2.6%). In the multivariate analysis, superior outcomes were associated with younger age, IgG subtype, complete hematological response at auto-HCT, Karnofsky score of 100%, international staging scoring (ISS) stage 1, HCT-comorbidity index (CI) 0, standard cytogenetic risk, auto-HCT in recent years, and use of lenalidomide maintenance. There were differences in the baseline characteristics and outcomes between registries. While the NRM was 1%-3% at 12 months worldwide, the OS at 36 months was 69%-84%, RI at 12 months was 12%-24% and PFS at 36 months was 43%-63%. The variability in these outcomes is attributable to differences in patient and disease characteristics as well as the use of maintenance and macroeconomic factors. In conclusion, worldwide data indicate that AHCT in MM is a safe and effective therapy with an NRM of 1%-3% with considerable regional differences in OS, PFS, RI, and patient characteristics. Maintenance treatment post-AHCT had a beneficial effect on OS.